2020
DOI: 10.1186/s41235-020-00232-7
|View full text |Cite
|
Sign up to set email alerts
|

What can an echocardiographer see in briefly presented stimuli? Perceptual expertise in dynamic search

Abstract: Background: Experts in medical image perception are able to detect abnormalities rapidly from medical images. This ability is likely due to enhanced pattern recognition on a global scale. However, the bulk of research in this domain has focused on static rather than dynamic images, so it remains unclear what level of information that can be extracted from these displays. This study was designed to examine the visual capabilities of echocardiographers-practitioners who provide information regarding cardiac inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The same is expectedly true for diagnostic judgments, for which we obtained a d 0 (AUC) of 0.98 (0.76) for first-or second-year medical students and of 2.58 (0.97) for our expert cardiologists, who were basically at ceiling in the current task. Our experts' d 0 was very similar to the d 0 of 2.57 reported by Carrigan et al, 40 and our novices' performance was considerable better than theirs, most probably due to their use of a general student sample, whereas our medical students might have already acquired some relevant knowledge.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The same is expectedly true for diagnostic judgments, for which we obtained a d 0 (AUC) of 0.98 (0.76) for first-or second-year medical students and of 2.58 (0.97) for our expert cardiologists, who were basically at ceiling in the current task. Our experts' d 0 was very similar to the d 0 of 2.57 reported by Carrigan et al, 40 and our novices' performance was considerable better than theirs, most probably due to their use of a general student sample, whereas our medical students might have already acquired some relevant knowledge.…”
Section: Discussionsupporting
confidence: 88%
“…found that experts use a more flexible strategy of inspecting the images. More relevant for this study is the research by Carrigan et al., 40 who employed an SDT approach and had observers judge the patient status of dynamic apical four-chamber views presented for various durations ranging from 1 to 10 s. They used d as a measure of diagnostic quality and found that experts could achieve a diagnostic quality of d=2.57, compared with d=0.21 for complete novices. This study uses a similar approach, but it combines it with eye tracking.…”
Section: Introductionmentioning
confidence: 99%
“…Combined, these results may reflect task demands, where retaining categorization information across both tasks was difficult. Further, the presentation time of 1500 ms meant that there were only 1–2 cardiac cycles observed, whereas, in clinical practice, more time can be taken to observe images (see Carrigan, Stoodley, Fernandez et al, 2020a). However, in the current study our goal was not to measure accuracy per se but to build upon our previous findings and investigate whether cue utilization could differentiate diagnostic performance as measured by accuracy.…”
Section: Discussionmentioning
confidence: 99%